Sex Hormone Decline and Amyloid β Synthesis, Transport and Clearance in the Brain. (23rd November 2016) - Duarte, A. C.; Hrynchak, M. V.; Gonçalves, I.; Quintela, T.; Santos, C. R. A.
Abstract : Sex hormones (SH) are essential regulators of the central nervous system. The decline in SH levels along with ageing may contribute to compromised neuroprotection and set the grounds for neurodegeneration and cognitive impairments. In Alzheimer's disease, besides other pathological features, there is an imbalance between amyloid β (Aβ) production and clearance, leading to its accumulation in the brain of older subjects. Aβ accumulation is a primary cause for brain inflammation and degeneration, as well as concomitant cognitive decline. There is mounting evidence that SH modulate Aβ production, transport and clearance. Importantly, SH regulate most of the molecules involved in the amyloidogenic pathway, their transport across brain barriers for elimination, and their degradation in the brain interstitial fluid. This review brings together data on the regulation of Aβ production, metabolism, degradation and clearance by SH.